Detoxification Of Lignocellulosic Hydrolysates By In situ Formation Of Fe(0) Nanoparticles On Activated Carbon - Hatika Kaco; Mohd Shaiful Sajab; Jude Santanaraj; Abdul Wahab Mohammad; Shuhaida Harun (North Carolina University, 2024)
Indexed by WOS/Scopus/ERA